1984
DOI: 10.1161/01.hyp.6.2_pt_2.i124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changes in sodium or potassium balance, and nephrectomy, on adrenal renin and aldosterone concentrations.

Abstract: An active form of renin was confirmed in the adrenal gland of rats. It had a molecular weight of 40,000, generated angiotensin I (AI) from natural renin substrate at pH 7.4, and was found at concentrations 30 to 60 times higher than plasma renin in rats on a normal diet. Changes in sodium diet induced changes in adrenal capsular renin concentration (high Na 2.21 +/- 0.34, normal Na 4.34 +/- 0.53, low Na 13.19 +/- 1.67 ng AI/mg protein/hr). A high potassium diet also increased adrenal capsular renin from 5.27 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 0 publications
4
48
0
Order By: Relevance
“…However, the mechanism by which adrenal renin controls aldosterone release is unclear. The parallel changes in adrenal renin and adrenal aldosterone observed in the present experiments also support a previous investigation (Doi et al, 1984) which indicated adrenal renin as a possible mediator of aldosterone realease. Under ACTH stimulation, ANP suppressed the adrenal renin and adrenal aldosterone, whereas no changes in these substances were observed in rats receiving ANP withont ACTH.…”
Section: Disc Nssionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, the mechanism by which adrenal renin controls aldosterone release is unclear. The parallel changes in adrenal renin and adrenal aldosterone observed in the present experiments also support a previous investigation (Doi et al, 1984) which indicated adrenal renin as a possible mediator of aldosterone realease. Under ACTH stimulation, ANP suppressed the adrenal renin and adrenal aldosterone, whereas no changes in these substances were observed in rats receiving ANP withont ACTH.…”
Section: Disc Nssionsupporting
confidence: 92%
“…However, similar changes in adrenal renin to adrenal aldosterone following ANP with and without ACTH were observed, so that the mechanisms by which ANP inhibits aldosterone release may involve suppression of the adrenal renin-angiotensin system. An increase in adrenal renin was demonstrated in nephrectomized rats (Doi et al, 1984, Inagami et al, 1984. In this condition, circulating angiotensin II must have been at an undetectable level.…”
Section: Disc Nssionmentioning
confidence: 97%
See 3 more Smart Citations